2017
DOI: 10.1007/s13205-017-0937-9
|View full text |Cite
|
Sign up to set email alerts
|

High-yield production of indole-3-acetic acid by Enterobacter sp. DMKU-RP206, a rice phyllosphere bacterium that possesses plant growth-promoting traits

Abstract: sp. DMKU-RP206 was isolated from rice leaves in Thailand and identified by the 16S rRNA gene and multilocus sequence (, , and genes) analysis. The bacterium was assessed on plant growth-promoting traits including indole-3-acetic acid (IAA) production. Phosphate solubilization, ammonia production, and antagonism to fungal plant pathogens, as well as siderophore production, were shown by this bacterium. However, only IAA production was focused on. The production of IAA by sp. DMKU-RP206 was optimized by statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 59 publications
(57 reference statements)
2
41
2
1
Order By: Relevance
“…A recent study has identified that Enterobacter sp. was able to secret IAA up to 5561.7 μg/mL using an optimized culture condition [58]. However, in this report, none of the strains was able to show zinc solubilization activity.…”
Section: Plos Onecontrasting
confidence: 54%
“…A recent study has identified that Enterobacter sp. was able to secret IAA up to 5561.7 μg/mL using an optimized culture condition [58]. However, in this report, none of the strains was able to show zinc solubilization activity.…”
Section: Plos Onecontrasting
confidence: 54%
“…These five strains have great potential in promoting plant growth (Fig. 4) and a large number of studies have proved the growth promoting ability of related strains 67,[72][73][74][75][76] . The dominant differential strains screened by non-culture methods (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has identified an Enterobacter sp. that was able to secret IAA up to 5561.7 μg/mL using an optimized culture condition [56]. However, in this report, none of the strains was able to show zinc solubilization activity.…”
Section: Discussionmentioning
confidence: 82%